The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1016/j.jgeb.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of hyaluronidase inhibitors in the neutralization of toxicity of Egyptian horned viper Cerastes cerastes venom

Abstract: Hyaluronidase ''venom spreading factor'' is a common component of snake venoms and indirectly potentiates venom toxicity. It may cause permanent local tissue destruction at the bite site/systemic collapse of the envenomated victim. The present study was performed to assess the benefits of inhibiting the hyaluronidase activity of Egyptian horned viper, Cerastes cerastes (Cc). The aqueous extracts of some medicinal plants were screened for their inhibitory effect on hyaluronidase activity of Cc venom. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
5
0
2
Order By: Relevance
“…HA inhibitors have also led to new therapeutic concepts in pathophysiological conditions, such as laryngeal or breast cancer treatment, that are associated with the hyaluronanhyaluronidase system 3,4,7 . Since the partial control of hyaluronidases possesses several important physiological functions, they have recently attracted considerable scientific interest as synthetic and natural inhibitors 4,[8][9][10][11][12] . Honey and bee products are natural materials whose antioxidant, anti-inflammatory and anti-tumoral efficacies vary depending on the flora from which they are produced.…”
Section: Introductionmentioning
confidence: 99%
“…HA inhibitors have also led to new therapeutic concepts in pathophysiological conditions, such as laryngeal or breast cancer treatment, that are associated with the hyaluronanhyaluronidase system 3,4,7 . Since the partial control of hyaluronidases possesses several important physiological functions, they have recently attracted considerable scientific interest as synthetic and natural inhibitors 4,[8][9][10][11][12] . Honey and bee products are natural materials whose antioxidant, anti-inflammatory and anti-tumoral efficacies vary depending on the flora from which they are produced.…”
Section: Introductionmentioning
confidence: 99%
“…Wahby et al. 14 proved that the RMAE, a potent hyaluronidase inhibitor, inhibited the spreading property of the Cc venom.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 12 , 13 Previously, we demonstrated that the rosemary leaves aqueous extract had potent hyaluronidase inhibitory effect among several medicinal plants tested in this study. 14 From this standpoint, the present study aims to evaluate the anti-venom properties of rosemary leaf aqueous extract against Egyptian Cerastes cerastes viper venom toxicity using both in vitro and in vivo assays.…”
Section: Introductionmentioning
confidence: 99%
“…Hialuronidase (TFU/mg) 4,72 x 10 5 ± 0,007 X -Reynals, 1936;Girish et al, 2004;Wahby et al, 2012b). Estudos recentes suportam a ideia da utilização de inibidores de hialuronidase ou ainda um soro específico para combater os efeitos desta enzima, em uma tentativa de diminuir os efeitos locais e sistêmicos do envenenamento (Girish e Kemparaju, 2006;Wahby et al, 2012a) A hialuronidase é uma enzima comumente encontrada na peçonha de várias espécies. Nas peçonhas de peixes já foi descrita em peixe-pedrae outras espécies de arraias (Poh et al, 1992;Magalhães et al, 2008;Madokoro et al, 2011), porém estas peçonhas, em geral, exibem uma atividade muito mais alta do que nas peçonhas de outras espécies.…”
Section: Atividade Enzimáticaunclassified
“…Dessa forma pode se inferir que as proteases juntamente com a hialuronidase, com atividade tão alta, pode ser o principal fator atuante nos sintomas locais do envenenamento por arraias de água doce. Estudos recentes suportam a ideia da utilização de inibidores de hialuronidase ou ainda um soro específico para combater os efeitos desta enzima, em uma tentativa de diminuir os efeitos locais e sistêmicos do envenenamento (Girish e Kemparaju, 2006;Wahby et al, 2012a) (Oliveira Jr., 2014).…”
Section: Atividade Enzimáticaunclassified